Polymorphisms in VDR gene in Tunisian postmenopausal women are associated with osteopenia phenotype. (August 2015) - Sassi, R.; Sahli, H.; Souissi, C.; Sellami, S.; Ben Ammar El Gaaied, A.
Abstract Objectives Osteopenia is characterized by intermediate values of bone mineral density (BMD) as compared to normal and osteoporotic subjects. BMD, a surrogate phenotype for osteoporosis, is influenced in part by genetic factors. Among the genes associated with BMD, the vitamin D receptor (VDR) was the first gene studied as a potential candidate associated with BMD in adult and postmenopausal bone loss. However, results are controversial. Methods To determine whether VDR polymorphisms ApaI and TaqI are associated with BMD, osteopenia, osteoporosis and low-impact fracture risk in North Africans, these genotypes were analyzed in 566 postmenopausal Tunisian women. Results In postmenopausal Tunisian women, the GT ApaI genotype seems to be protective against osteoporosis development (p = 0.02; odds ratio = 0.54). Moreover, the presence of the combined GT/TT genotype of ApaI and TaqI polymorphisms is more frequent in normal BMD women than in osteoporotic women (p = 0.00; odds ratio = 0.41). Interestingly, the GG ApaI genotype is associated with osteopenia development (p = 0.02; odds ratio = 1.86) and also the TT TaqI polymorphism (p = 0.02; odds ratio = 1.53). The GG ApaI genotype is associated with a three times risk of vertebral fracture. Conclusions The ApaI polymorphism showed an association with osteopenia and low-impact vertebral fracture incidence but not with osteoporosis. The TaqI polymorphism is associated specifically with the osteopenia phenotype. The presence of the two polymorphisms increases the risk to develop osteopenia in postmenopausal Tunisian women. Osteopenia seems to be genetically determined. However, osteoporosis is the result of interaction between genetic and environmental factors.